Toleransi Beragama Dalam Pendidikan Multikultural di SMA Negeri 1 Bolangitang Barat - Berahima, Nurmutmainna; Wantu, Hasyim (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2020)
ABSTRACK This Study aims to determine the form religious tolerance in multicultural education at SMA Negeri I Bolangitang Barat North Bolaang Mongondow regency, the proess of religious tolerance in multicultural education at SMA 1 Bolangitang Barat North Bolaang Mongondow regency and supporting and inhibiting factors in the processof inculcating religious tolerance in multicultural education at West Bolangitang I High School. This type of research is descriptive qualitative. In collecting data researches used interview, observation, and documentation methode. The result of the study show the forms of religious tolerance that teachers do in school, namely 1.) by getting all students who are both Muslim and Christian to have an attitude of Tasamuh (tolerance) by instilling mutual repect, mutual understanding, respect for interfaith, an adeucator also instill agood attitude between students in the school enviroment. 2.) the Process of religious tolerance education in West Bolangitang I High School namely by providing opportunities for all students to attend religious learning according to their respective religious understanding. Learn to accept in differences, build mutual trust, maintain mutual understanding between teacher and students. Uphold the attitude of mutual love between each other, as well as guide and motivate students in maintaining an attitude of religious tolerance. 3.) Supporting Factors in inculcating religious tolerance values in multicultural namely the existence of adequate facilities for learning according to their respective religions and beliefs, good cooperation between school residents in religious activities and suppoting books that supports students knowledge about religious tolerance, while the inhibiting factor namely lack of learning facilities supports, lack of educators, and limited time available in teaching. Keywords : Religious Tolerance, Multicultural Education, SMA Negeri I Bolangitang Barat